Analisis Perhitungan Nilai Rata-Rata Pergeseran Verifikasi Geometri Menggunakan EPID Pada Pasien Kanker Payudara Di Sub Instalasi Radioterapi RSUP Prof. Dr. I.G.N.G Ngoerah - I Gusti Putu Agung Wisnu Putra; Ni Putu Rita Jeniyanthi; Ngakan Putu Daksa Ganapati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Breasts are organs that play a role in the lactation process. In men, this organ does not develop and does not have a function in the lactation process like in women. According to. cancer is characterized by the growth of abnormal cells beyond normal limits and can attack adjacent parts of the body or metastasize to other organs which can result in death for the sufferer. Cancer is also called malignant tumor and neoplasm. Breast cancer sufferers often find out about their disease too late, so they come to the hospital when it is in the final stage. Early detection is very necessary so that breast cancer sufferers can be treated more quickly. The prevalence of cancer in Bali Province in 2018 was 2.3 per 1000 population. This incidence increased compared to the 2013 Riskesdas results of 2.0 per 1000 population (Riskesdas, 2018). The total number of breast cancer cases recorded in the Medical Records Installation at Sanglah General Hospital Denpasar for the period 1 January – 31 December 2022 and which met the inclusion criteria was 70 people with a monthly average of 5.83%, around 6 patients. Inclusion criteria are breast cancer patients with stage II-IV and who have had a mastectomy. Based on a report from the Bali Province Integrated Disease Survey, it was found that the incidence of breast cancer in 2019 was 437 cases. especially in Denpasar City, the incidence of breast cancer was 293 cases. Denpasar City is an area that has the highest incidence of breast cancer in Bali.